B. abortus RNA induces MHC-I retention in the Golgi apparatus via TLR8 and by disrupting the acidification of this compartment - Milillo, María Ayelén (2017)
Despite the cytotoxic CD8+ T cell responses elicited by Brucellaabortus, this pathogen is able to survive inside macrophages andgenerate a chronic infection. B. abortus infection of human monocytesdown-modulates the IFN-γ-induced MHC-I cell surface expressionby retaining these molecules in the Golgi apparatus (GA).We have recently demonstrated that B. abortus RNA is the bacterialcomponent involved in this phenomenon. Thus, the aim of this studywas to further characterize the receptor and mechanisms implicatedin MHC-I down-modulation. Endo/phagolysosomal Toll-like receptors(TLR) 3, 7 and 8 are the most known receptors capable ofrecognizing RNA. We had previously discarded TLR3 consequently,to study whether TLR7 and/or TLR8 were involved in the B. abortusRNA-mediated MHC-I down-modulation, THP-1 cells or murinebone marrow macrophages (BMM) were treated with human TLR-7 or TLR-8 agonists in the presence of IFN-γ for 48 h. Then, theexpression of MHC-I molecules was evaluated by flow cytometry.Surpringsily, TLR8 (p<0.05) but not TLR7 was the receptor involvedin this phenomenon. Mice do not have a functional TLR8 insteadTLR7 performs its function. To confirm that TLR7/8 was the receptorlinked to MHC-I down-modulation, TLR7 KO BMM were infectedwith B. abortus or treated with its RNA. In both cases, MHC-Idown-modulation was abolished as well as the antigen presentationto CD8+ T cells. Concerning the retention mechanism, we confirmedthat neither MHC-I protein degradation nor a modification of itsmRNA expression was involved. Rather, we demonstrated that theionophore monensin (which impedes the proper acidification of GAcisternae) mimicked B. abortus RNA-induced retention of MHC-I inGA (p<0.05). Overall, these results indicate that B. abortus RNA,viaTLR8 and probably due to an inhibition of Golgi acidification, inhibitsMHC-I expression. Thus, bacteria can hide within infected cellsand avoid the immunological surveillance of cytotoxic CD8+ T cells.